2019
DOI: 10.1002/elan.201900200
|View full text |Cite
|
Sign up to set email alerts
|

Small Size Effect and Concentration Response of Gold Nanoparticles in Electrochemiluminescence Reaction

Abstract: Recent reports have used gold nanoparticles (AuNPs) as a co‐reactant for the electrochemiluminescence (ECL) reaction of ruthenium complex. However, understanding the size effect of AuNPs on ECL reaction is very meaningful to explore its unknowns and develop its applications at the molecular level. In this paper, we examined the behavior of various small‐size AuNPs in ECL reaction, focusing on changes in ECL caused by AuNPs size and reasons for this change. Although the luminescence spectra and excitation poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Under this circumstance, the ECL signal of CdS quantum dots recovers and the off-on detection strategy of Aflatoxin B1 was constructed [36]. A linear relationship between ECL signal strength and Aflatoxin B1 concentration can be established [37]. To determine Aflatoxin B1 concentration in crunched peanut samples [38], this research showed an ultrasensitive ECL biosensor for detecting Aflatoxin B1 which offers a new venue for monitoring the Aflatoxin B1 concentration in food.…”
Section: Introductionmentioning
confidence: 98%
“…Under this circumstance, the ECL signal of CdS quantum dots recovers and the off-on detection strategy of Aflatoxin B1 was constructed [36]. A linear relationship between ECL signal strength and Aflatoxin B1 concentration can be established [37]. To determine Aflatoxin B1 concentration in crunched peanut samples [38], this research showed an ultrasensitive ECL biosensor for detecting Aflatoxin B1 which offers a new venue for monitoring the Aflatoxin B1 concentration in food.…”
Section: Introductionmentioning
confidence: 98%